1995
DOI: 10.1073/pnas.92.5.1749
|View full text |Cite
|
Sign up to set email alerts
|

Human RanGTPase-activating protein RanGAP1 is a homologue of yeast Rna1p involved in mRNA processing and transport.

Abstract: RanGAPI is the GTPase activator for the nuclear Ras-related regulatory protein Ran, converting it to the putatively inactive GDP-bound state. Here, we report the amino acid sequence of RanGAPI, derived from cDNA and peptide sequences. We found it to be homologous to murine Fugl, implicated in early embryonic development, and to Rnalp from Saccharomyces cerevisiae and Schizosaccharomyces pombe. Mutations of budding yeast RNA] are known to result in defects in RNA processing and nucleocytoplasmic mRNA transport.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
174
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(177 citation statements)
references
References 30 publications
1
174
0
2
Order By: Relevance
“…If its primary function is in nuclear export, the cytoplasmic localization of Gle2p may seem paradoxical. However, similar observations have been reported for Rnalp, a GTPase-activating protein for Gsplp/Ran/TC4 transport activity (Bischoff et al, 1995;Corbett et al, 1995). Rnalp is localized both in the cytoplasm and at NPCs, and the rnal-l mutant has a rapid and penetrant poly(A)+ RNA export block (Hopper et al, 1990;Amberg et al, 1992;Koepp et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
“…If its primary function is in nuclear export, the cytoplasmic localization of Gle2p may seem paradoxical. However, similar observations have been reported for Rnalp, a GTPase-activating protein for Gsplp/Ran/TC4 transport activity (Bischoff et al, 1995;Corbett et al, 1995). Rnalp is localized both in the cytoplasm and at NPCs, and the rnal-l mutant has a rapid and penetrant poly(A)+ RNA export block (Hopper et al, 1990;Amberg et al, 1992;Koepp et al, 1996).…”
Section: Discussionmentioning
confidence: 71%
“…Such pleiotropism is particularly pronounced in S. cerevisiae cells carrying temperature-sensitive mutations in the RNA1 gene which were first described by Hartwell (30) 3 decades ago. Only recently it was shown that Rna1p acts as a GAP for Gsp1p and participates in protein import into S. cerevisiae nuclei both in vitro and in vivo (20,31,32). The homologous protein from S. pombe, rna1p, possesses GAP activity for Gsp1p (31) and in contrast to S. cerevisiae Rna1p also stimulates the GTP hydrolysis mediated by human Ran (23,31).…”
mentioning
confidence: 99%
“…The GTP/GDP cycle is regulated by two auxiliary proteins, a GTPase activating protein (GAP) which stimulates the intrinsic GTPase activity of Ran by several orders of magnitude and a guanine nucleotide exchange factor which markedly accelerates the GTP for GDP exchange rate on Ran. The only guanine nucleotide exchange factor for Ran known to date is the nuclear protein RCC1, whereas the only RanGAP identified so far is a cytosolic protein (17)(18)(19)(20). The strictly compartmentalized organization of the two principle regulators, RanGAP and RCC1, indicates that Ran shuttles between the cytoplasm and the nucleus to interact with its regulator proteins and that a gradient of Ran⅐GTP exists across the nuclear envelope (for review see Refs.…”
mentioning
confidence: 99%
“…Like other Ras-like proteins, Ran has a low intrinsic GTPase activity. Hydrolysis of bound GTP is stimulated by a RanGAP [66] which was found to be a functional homologue of the cytoplasmic yeast protein Rnalp [63,67,68]. Mutants in RCC1 and its budding yeast homologue, PRP20, display pleiotropic defects.…”
Section: Ranmentioning
confidence: 99%
“…2). If RNA export is a mirror image of protein import, a second set of a nuclear GAP and a cytoplasmic GEF have to be postulated but they have not been found yet [67,68]. Using recombinant yeast proteins, it was shown that addition of GTP-loaded Gsplp (the essential yeast Ran), and not of Gsplp-GDP, caused dissociation of a complex consisting of FXFG repeats of Nuplp, NRct, and NR[3, as well as of a complex consisting of import substrate, NRct, and NRI3 [32].…”
Section: Ranmentioning
confidence: 99%